Adaptasi Anatomis Tanaman Kedelai Varietas Slamet Akibat Perbedaan Ketinggian Tempat - Juwarno Juwarno; Muachiroh Abbas; Eddy Tri Sucianto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
A research on the “Anatomical Adaptation of Soybean ‘Slamet’ in Various Altitudes” has been conducted. The research was aimed to traced anatomical adaptation of soybean ‘Slamet’ in various altitude and to proved altitude give the anatomical adaptation to soybean ‘Slamet’. The result of this research showed that altitude has caused the increase of leaf mesophyll thickness. The different altitude does not affect the cuticle thickness, length and width of stomata, stomatal and trichomatal density per mm2 of leaf area. The altitude affected the anatomical adaptation of soybean ‘Slamet’ was 250 m above sea level with the average mesophyll thickness of 112.40 µm. A research entitled on the “Anatomical Adaptation of Soybean ‘Slamet’ Variety Plant Because of in Various Altitudes Differentiation” have has been conducted. The research was aimed was to traced anatomical adaptation of soybean ‘Slamet’ variety plant because of in various altitude differentiation and to proved altitude differentiation give the anatomical adaptation of to soybean Slamet variety plant. The result of the this research showed that altitude differentiation has caused the increase of leaf mesophyll thickness raise of soybean Slamet variety leaf. The different altitude differentiation does not caused of affect the cuticle thickness, the length and width stomata, the stomatal and trichomatal density per mm2 leaf area. The altitude most affected on the anatomical adaptation of soybean ;Slamet; variety was 250 m above sea level with the most average mesophyll thickness of 112.40 µm.A research on the “Anatomical Adaptation of Soybean ‘Slamet’ in Various Altitudes” has been conducted. The research was aimed to traced anatomical adaptation of soybean ‘Slamet’ in various altitude and to proved altitude give the anatomical adaptation to soybean ‘Slamet’. The result of this research showed that altitude has caused the increase of leaf mesophyll thickness. The different altitude does not affect the cuticle thickness, length and width of stomata, stomatal and trichomatal density per mm2of leaf area. The altitude affected the anatomical adaptation of soybean ‘Slamet’ was 250 m above sea level with the average mesophyll thickness of 112.40 µm. A research entitled on the “Anatomical Adaptation of Soybean ‘Slamet’ Variety Plant Because of in Various Altitudes Differentiation” have has been conducted. The research was aimed was to traced anatomical adaptation of soybean ‘Slamet’ variety plant because of in various altitude differentiation and to proved altitude differentiation give the anatomical adaptation of to soybean Slamet variety plant. The result of the this research showed that altitude differentiationhas caused the increase of leaf mesophyll thickness raise of soybean Slamet variety leaf. The different altitude differentiation does not caused of affect the cuticle thickness, the length and width stomata, the stomatal and trichomatal density per mm2 leaf area. The altitude most affected on the anatomical adaptation of soybean ;Slamet;varietywas 250 m above sea level with the most average mesophyll thickness of 112.40 µm.